2022
DOI: 10.3390/jpm12122026
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Systemic Immune-Inflammation Index and Symptom Severity Score for Sepsis and Systemic Inflammatory Response Syndrome in Odontogenic Infections

Abstract: Acute Odontogenic Infections (OI) are the leading cause of emergency visits and hospitalizations to the maxillofacial department, and may induce systemic inflammatory complications. Increasing numbers of OI patients need extended hospitalizations, various treatments, and intensive care. The Symptom Severity score (SS) helps doctors assess the likelihood of infection and admission complications. Systemic Immune-inflammation Index (SII) is a biomarker-based inflammatory prognosis score. It was hypothesized that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Inflammatory activity can be assessed through a series of indicators derived from peripheral blood tests, such as the white blood cells, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and C -reaction protein that have been previously reported by scholars [ 36 , 37 ]. The SII was developed and combined three biomarkers of peripheral blood, including platelet, neutrophil, and lymphocyte count, presents as a comprehensive and robust indicator, which thoroughly sum up the balance of the host inflammatory and immunological status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory activity can be assessed through a series of indicators derived from peripheral blood tests, such as the white blood cells, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and C -reaction protein that have been previously reported by scholars [ 36 , 37 ]. The SII was developed and combined three biomarkers of peripheral blood, including platelet, neutrophil, and lymphocyte count, presents as a comprehensive and robust indicator, which thoroughly sum up the balance of the host inflammatory and immunological status.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent retrospective study conducted by Pricop et al a group of 108 patients with acute odontogenic infections were observed. The study revealed that the ratio of patients developing sepsis was accurately predicted by the SII score, which also demonstrated the potential to predict the development of systemic inflammatory response syndrome [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a few studies have investigated the SII index in odontogenic cervicofacial phlegmons. Furthermore, in the case of deep odontogenic infections, its applicability has not yet been clearly established [ 29 ]. The values of the SII in our study significantly decreased after the surgical approach and pharmacological treatment of the cervicofacial phlegmons ( p = 0.012).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing attention has been given to finding an evaluation system that can predict the severity of OMHNSI. Although, acute physiology and chronic health score are used to indicate the severity of clinical conditions for patients (Pricop et al, 2022). However, they are complicated and inconvenient to be calculated.…”
Section: Discussionmentioning
confidence: 99%